Halictus hedini hedini (Hymenoptera: Halictidae) newly recorded from Japan, revealed by DNA barcoding and morphology - Murao, Ryuki; Gibbs, Jason (Journal of Melittology, 2019)
Halictus hedini hedini Blüthgen is newly recorded from Japan. The species had been previously mistaken for the Holarctic species H. rubicundus (Christ), which is removed from the Japanese fauna. Halictus hedini hedini was previously known from Eastern and Central Asia. Halictus hedini hedini is similar to H. rubicundus, but is separated by the first metasomal tergum with coarse and deep punctures in both sexes and the male flagellum ventrally with a fringe of short hairs. A key to Japanese species of Halictus is provided. DNA barcodes, phenology, and floral records from Japan are reported.